Rancang Bangun Sistem Informasi Learning Management System meggunakan Metode Waterfall dengan Framework Laravel - Ferdy Syahlan Susilo; Eko Hariyanto; Rahmad Budi Utomo (Cattleya Darmaya Fortuna, 2026)
Learning Management System (LMS) is a technology-based system designed to support online learning processes. This study aims to design and develop a web-based LMS information system using the Waterfall method and the Laravel framework as an effort to enhance internship training at PT. Kodinglab Integrasi Indonesia. The research method involves several stages, including requirements analysis, system design, implementation, and testing. The objective of this study is to demonstrate that the developed LMS can assist mentors and interns in managing training materials, monitoring progress, and assessing learning outcomes digitally. This system facilitates the learning process and supports self-directed learning